(untitled) (Research, Society and Development, 2021)
The dermoid is a cystic mass of normal skin-like consistency located in an anatomically abnormal region, containing cutaneous attachments such as hair, stratified squamous epithelium, hair follicles, sebaceous glands, and other structures. The aims of this article is to report a case of unilateral third eyelid dermoid in a 3-week-old bovine, addressing the diagnostic aspects, as well as the importance of therapeutic conduct for animal maintenance and quality of life. Diagnostic confirmation was carried out through histopathological analysis, with the excision of the mass performed with elevation of the third eyelid and wedge incision in the region of the lesion, obtaining surgical success and without recurrences. It is concluded that the dermoid cyst, even though it is of low occurrence in bovine herds, should not be neglected, since there are great ophthalmic complications caused by its permanence in the eyeball. This study emphasizes the importance of early diagnosis and therapeutic conduct, for maintaining the animal’s quality of life and maintaining zootechnical gains for farm animals.